2011
DOI: 10.1111/j.1600-0528.2011.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Caries in adolescence – influence from early childhood

Abstract: Early caries experience, consumption of sweets at an early age and mother's self-estimation of her oral health care as being less good to poor are associated with approximal caries in adolescents. The study indicates that caries determinants identified during early childhood have a strong impact on approximal caries in adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 24 publications
4
57
0
4
Order By: Relevance
“…Covariates for multivariate models were based on theoretical potential to modify the association between exposure and outcome of interest based on the literature [11,30,31], and exploratory stepwise analyses comparing unadjusted to adjusted ORs after inclusion of potential covariates. X 2 and Wald F-statistics were inspected to test for unadjusted associations and overall model fit, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Covariates for multivariate models were based on theoretical potential to modify the association between exposure and outcome of interest based on the literature [11,30,31], and exploratory stepwise analyses comparing unadjusted to adjusted ORs after inclusion of potential covariates. X 2 and Wald F-statistics were inspected to test for unadjusted associations and overall model fit, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies report no significant association between either intake of sugars confectionery or sweet snacks and dental caries incidence (Leroy et al, 2005;Tamaki et al, 2009). Of the studies identified in the update search one reports an association between frequency of consumption of sugars confectionary at age one year and dental caries development at age 15 years (Alm et al, 2012) and the other in children and adolescents with cerebral palsy also found a significant association between higher frequency of sugars consumption and dental caries (Ferreira et al, 2011). Of the studies that did not adjust for tooth brushing one indicates that the number of between meal snacks containing more than 10% sugars is associated with two-year dental caries increment, but not three-year caries increment (Wilson & Ashley, 1989) and the other two indicate no association between sugars confectionery and snack consumption and dental caries risk.…”
Section: Sugars-sweetened Beverages and Bmimentioning
confidence: 99%
“…The data on measures of dietary exposure, caries incidence/prevalence and risk assessment methods were insufficiently comparable to enable a meta-analysis to be performed. Two additional studies were identified in the update search, both of which adjusted their results for tooth brushing (Ferreira et al, 2011;Alm et al, 2012) (Oral health review p40 and p70; Update search table 234) 6.68. Three studies report an association between higher frequency of consumption of sugars in confectionery and greater dental caries incidence (Mattila et al, 2001;Mattila et al, 2005;Kallestal & Fjelddahl, 2007;Ollila & Larmas, 2007).…”
Section: Sugars-sweetened Beverages and Bmimentioning
confidence: 99%
“…Diet, and especially sucrose consumption, is one of the main etiological factors in the caries process [Anderson et al, 2009;Alm et al, 2012]. Together with the cariogenic bacteria, sucrose forms a matrix for dental biofilm, but the exact role of sucrose in the etiology of dental caries is still the subject of debate [Arola et al, 2009].…”
mentioning
confidence: 99%
“…The effect of sugars on caries starts at an early age and continues towards adolescence [Alm et al, 2012]. The factors determining the actual sugar intake are not fully known, and it has been suggested that both environmental and genetic factors may play a role in this respect [Drewnowski, 2000;Qi and Cho, 2008;Coldwell et al, 2009;Overberg et al, 2012].…”
mentioning
confidence: 99%